INOVASI PELAYANAN PUBLIK: ANALISIS BIBLIOMETRIK TERHADAP PERKEMBANGAN DAN TREN PENELITIAN - Monica, Reza; Permatasari, Indah; Lionardo, Andries; Budiyanto, M. Nur (FISIP Universitas Malikussaleh, 2024)
This research presents a bibliometric analysis of the development and collaboration in public service innovation research from 2014 to 2023. Data were obtained from the Scopus database using the keyword